2020
DOI: 10.1111/ajo.13256
|View full text |Cite
|
Sign up to set email alerts
|

A routine third trimester growth ultrasound in the obese pregnant woman does not reliably identify fetal growth abnormalities: A retrospective cohort study

Abstract: Background In response to the challenges of assessing fetal growth in obese women, guidelines recommend routine third trimester ultrasound scans. Aim The aim of this study was to assess the diagnostic performance of this routine scan in obese women (body mass index (BMI) ≥ 35 kg/m2). Methods A retrospective cohort study of 1008 pregnancies with maternal BMI ≥ 35 kg/m2 born after 37 weeks gestation at a Victorian hospital from 2015 to 2017. Multiple pregnancies and those affected by diabetes were excluded. Grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Especially for large fetuses, an accurate and precise BW prediction is required but is often not provided by conventional 2D models that do not consider soft tissue 33 . BW prediction, especially the detection of large for gestational age (LGA) fetuses, can be complicated by obesity 34 . Neel et al demonstrated that the sensitivity for detecting LGA at birth by routine 2D scan in obese patients with a BMI greater than 35 kg/m 2 was 61.0% (119 of 195), and the positive predictive value was 54.8% 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for large fetuses, an accurate and precise BW prediction is required but is often not provided by conventional 2D models that do not consider soft tissue 33 . BW prediction, especially the detection of large for gestational age (LGA) fetuses, can be complicated by obesity 34 . Neel et al demonstrated that the sensitivity for detecting LGA at birth by routine 2D scan in obese patients with a BMI greater than 35 kg/m 2 was 61.0% (119 of 195), and the positive predictive value was 54.8% 34 .…”
Section: Discussionmentioning
confidence: 99%
“…BW prediction, especially the detection of large for gestational age (LGA) fetuses, can be complicated by obesity 34 . Neel et al demonstrated that the sensitivity for detecting LGA at birth by routine 2D scan in obese patients with a BMI greater than 35 kg/m 2 was 61.0% (119 of 195), and the positive predictive value was 54.8% 34 . In our opinion, these results need improvement, and new solutions such as FLV models might be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially important in mothers with obesity due to a correlation between maternal excess weight and fetal macrosomia, as well as higher incidence of small for gestational age (SAGA) neonates (< 10 percentile) born to mothers after bariatric surgery [60,61]. As far as the additional late-third trimester ultrasound test (i.e., between 34 +0 and 36 +6/7 weeks of gestation) is concerned, the findings of studies published so far have not validated the need for such a test [62][63][64]. When it comes to low birthweight fetuses, the sensitivity and the positive predictive values of ultrasound evaluation of the fetal weight at that stage of pregnancy are 8.1-32% and 58.5-100%, respectively, while for fetuses with birthweight of > 90 percentile the values are 38.6-87.1% and 30.2-77.1%, respectively [62][63][64].…”
Section: Third Trimester Ultrasoundmentioning
confidence: 99%
“…As far as the additional late-third trimester ultrasound test (i.e., between 34 +0 and 36 +6/7 weeks of gestation) is concerned, the findings of studies published so far have not validated the need for such a test [62][63][64]. When it comes to low birthweight fetuses, the sensitivity and the positive predictive values of ultrasound evaluation of the fetal weight at that stage of pregnancy are 8.1-32% and 58.5-100%, respectively, while for fetuses with birthweight of > 90 percentile the values are 38.6-87.1% and 30.2-77.1%, respectively [62][63][64]. The abovementioned percentile values are the reason why, in a group of mothers with obesity, a significant number of fetuses with birthweight of <10 percentile remain undiagnosed, whereas in case of excess fetal growth, approximately half of the readings are false positive.…”
Section: Third Trimester Ultrasoundmentioning
confidence: 99%